OPERA AND ITALIAN IDENTITY: THE LONG VIEW - Stefano CASTELVECCHI (Studia Universitatis Babeş-Bolyai. Musica)
The nineteenth century is generally acknowledged as the period in which modern ideas of nation and nationalism crystallised; it is also seen as the period in which those ideas played a part in the process of Italian unification. The role that opera may have played in that process has been the object of much debate. Here I take a longer view, and begin to explore the more elusive ways in which music and opera may have contributed to the emergence of an Italian identity (an important condition for any thought about political unification) in the eighteenth century.